Pengembangan E-Modul Pembelajaran Berbasis Etnosains Pembuatan Batik Jambi pada Kurikulum Merdeka untuk Meningkatkan Keterampilan Literasi Sains Siswa SMA : (Development of E-Module Learning Based on Ethnoscience Making Jambi Batik in Independent Curriculum to Improve Science Literacy Skills of High School Students) - Febrina, Wahyuni; Yelianti, Upik; Wicaksana, Ervan Johan (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
Improving students science literacy skills is one of the important focuses in education today. This study seeks to integrate local values, especially Jambi batik making, into science learning through the development of an E-Module based on ethnoscience. Through a series of development stages, this E-Module was then tested for validity, practicality, and effectiveness in improving the science literacy skills of high school students. This study uses the Research & Development (R&D) method by applying the ADDIE model. Research & Development aims to produce a product, and in this context, the product developed is an E-Module learning based on ethnoscience of making Jambi batik to improve the science literacy skills of high school students. The ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The type of data in this study is qualitative and quantitative. The results of the validation from material experts obtained a percentage of 94,16% with a very feasible category. Furthermore, the results of the validation of media experts obtained a percentage of 91,8% with a very feasible category. The results of the biology teacher assessment obtained 91% with a very feasible category. The results of the trial to see the response of students in small groups obtained a percentage of 88,49% with a very good category and the trial of large groups obtained a percentage of 93.7% with a very good category. Thus, this study makes a positive contribution to improving the science literacy skills of high school students and promoting the sustainability of cultural heritage through integrated learning. Abstrak. Peningkatan keterampilan literasi sains siswa menjadi salah satu fokus penting dalam Pendidikan saat ini. Penelitian ini berupaya mengintegrasikan nilai-nilai lokal, khususnya pembuatan batik jambi, ke dalam pembelajaran sains melalui pengembangan E-Modul berbasis etnosains. E-Modul ini kemudian diuji validitas, kepraktisan, dan efektifitasnya dalam meningkatkan keterampilan literasi sains siswa SMA. Penelitian ini menggunakan metode Research & Development (R&D) dengan menerapkan model ADDIE yang terdiri dari tahap Analysis, Design, Development, Implementation, dan Evaluation. Research & Development bertujuan untuk menghasilkan produk, dalam konteks ini produk yang dikembangkan adalah E-Modul pembelajaran berbasis etnosains pembuatan batik jambi untuk meningkatkan keterampilan lierasi sains siswa SMA. Jenis data penelitian adalah kualitatif dan kuantitatif. Hasil validasi dari ahli materi diperoleh sebesar 84,72% dengan kategori sangat layak. Selanjutnya hasil validasi ahli media diperoleh 90,6% dengan kategori sangat layak. Hasil penilaian guru biologi diperoleh sebesar 96,25% dengan kategori sangat layak. Hasil uji coba untuk melihat respon peserta didik pada kelompok kevil diperoleh persentase sebesar 87,96% dengan kategori sangat baikdan uji coba kelompok besar diperoleh persentase sebesar 93,9% dengan kategori sangat baik. Dengan demikian, penelitian ini memberikan kontribusi positif terhadap peningkatan keterampilan literasi sains siswa SMA dan mempromosikan keberlanjutan warisan budaya melalui pembelajaran yang terintegritas pada kearifan lokal.